Methodological Considerations for the Temporal Summation of Second Pain - Eckert, Nathanial R. (J Pain, 2017)
Temporal summation of second pain (TSSP) is a psychophysical indication of a central pain encoding mechanism, potentially enhanced in pathological pain conditions. Low frequency repetitive stimulation of unmyelinated (C) nociceptors results in a progressive increase of pain intensity when thermal stimulation intensity remains constant. However, when using different methods of nociceptive delivery to the skin, both regularity and rate of pain enhancement with repetition varies between experiments. Specifically, repetitive ramping up and down from a neutral to a painful temperature has produced weak and inconsistent pain summation. In contrast, repetitive contact of the skin with a preheated probe has generated substantial pain summation. In the present study, TSSP by the intermittent contact (IC) with a preheated thermode and constant contact, ramp and hold (CC) methods were compared during 10 iterations of stimulation of glabrous skin of the hand or hairy forearm skin, with an onset to onset interval of 3.3 sec and stimulus interval of 0.8 sec. Significantly greater TSSP was observed for IC stimulation at both sites (p < .001). Differential activation of myelinated and unmyelinated nociceptors by ramping and tapping may account for different rates of temporal summation of heat pain. PERSPECTIVE: This article presents direct evidence suggesting the constant contact, ramp and hold stimulus may underestimate the level of Temporal Summation of Second Pain. This evidence suggests the re-evaluation of stimulation techniques utilized for Temporal Summation tests, especially within clinical models.